A habitat analog approach establishes native plant communities on green roofs. Issue 9 (13th September 2021) - Ksiazek‐Mikenas, Kelly; Chaudhary, V. Bala; Larkin, Daniel J.; Skogen, Krissa A.
Abstract: Novel habitats can support biodiversity by amending what has been lost through urban development. However, the effects of fragmentation, disturbance, and altered availability of resources in cities can prevent many local plant species from establishing and persisting. Novel habitats like green roofs could be colonized by native plants if species could overcome particularly harsh environmental conditions. To do so, green roofs could be designed using a habitat analog approach wherein natural habitats with similar abiotic characteristics inform the potential species pool. In this study, we tested the efficacy of using a habitat analog approach to establish native plant communities on green roofs. We surveyed vegetation in 18 dry prairies of three subtypes (gravel hill, dolomite, and sand) and planted replicates of two communities (sand prairie and rock prairie, which combined gravel hill and dolomite) on green roofs to determine which prairie was the most suitable analog. We investigated the effect of three environmental variables on plant establishment, survival, and growth: soil continuity (continuous soil vs. isolated trays), planting method (seeds vs. pre‐grown seedlings), and the addition of native arbuscular mycorrhizal (AM) fungi. We determined the most suitable habitat analog and measured the effect of the environmental variables by conducting vegetation surveys in the experimental roof plots for three years. The experimental rock prairie communities more closely resembled the target than did the sand prairies, supporting the hypothesis that shared soil properties are important for establishing analogous plant communities in novel habitats. At the community level, survival and growth were higher in continuous soil, highlighting the importance of belowground components of constructed habitats. We found no effect of planting method or addition of native AM fungi on plant survival or growth. Overall, our results support using a habitat analog approach to select native species that support biodiversity in constructed novel habitats like green roofs.